Circuit interrogation in freely moving animals. (January 2019) - Wallace, Damian; Kerr, Jason
Developments in imaging tools are making it possible to record activity from both large neuronal populations and subcellular components in freely moving animals. Although these developments are enabling relationships between brain activity and complex behaviors to be explored, many challenges need to be overcome before the potential of the freely moving animal can be fully utilized.